Concept Of Viruddha Ahara (Incompatible Food) In Today’s Perspective - Kumar, Pathak Arvind; Rashmi, Diwan; Reetika, Pathak (International Research Journal of Ayurveda & Yoga, 2021)
According to Ayurveda Ahara (Food) is the most important thing for healthy life and type of Ahara (Food) we eat affect our body as well as mind. Nowadays people are adopting sedentary life style. Also, the craze of fast food is increasing everywhere. The change in food habit, lack of knowledge about proper nutrition are causative factors for many diseases. Viruddha Ahara (Incompatible food) is one of the unique concepts described in Ayurveda. Ayurveda clearly defines that certain diet and its combination which interrupts the metabolism of body tissues, which inhibits the process of formation of Dhatus and which have opposite property to the Dhatus are called as Viruddha Ahara (Incompatible food). Ahara (Food) is the most important essential requirement of all living beings. Nowadays there is increased prevalence of lifestyle disorders, in which faulty dietary habits plays an important role. That’s why knowledge of Viruddha Ahara (incompatible food) is very important in present era. In this article Viruddha Ahara (incompatible food) discussed by our Ayurveda text are represented and reviewed.